2021
DOI: 10.1186/s13053-020-00160-z
|View full text |Cite
|
Sign up to set email alerts
|

Familial pancreatic cancer with PALB2 and NBN pathogenic variants: a case report

Abstract: Background Family history is one of the risk factors for pancreatic cancer. It is suggested that patients with pancreatic cancer who have a familial history harbor germline pathogenic variants of BRCA1 and/or BRCA2 (BRCA1/2), PALB2, or ATM. Recently, some germline variants of familial pancreatic cancers (FPCs), including PALB2, have been detected. Several countries, including Japan, perform screening workups and genetic analysis for pancreatic cancers. We have been carrying out active surveilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…A family history of cancer was an independent risk factor for both pancreatic cancer and high-risk sIPMN (Table 4 and Supplemental Table 1, http://links.lww.com/MPA/A962). This suggested the involvement of genetic factors in IPMN and pancreatic cancer 24 . Intraductal papillary mucinous neoplasm can become a prognostic factor for hereditary cancer syndromes, as shown in Supplemental Table 5 http://links.lww.com/MPA/A962 25–27 .…”
Section: Discussionmentioning
confidence: 97%
“…A family history of cancer was an independent risk factor for both pancreatic cancer and high-risk sIPMN (Table 4 and Supplemental Table 1, http://links.lww.com/MPA/A962). This suggested the involvement of genetic factors in IPMN and pancreatic cancer 24 . Intraductal papillary mucinous neoplasm can become a prognostic factor for hereditary cancer syndromes, as shown in Supplemental Table 5 http://links.lww.com/MPA/A962 25–27 .…”
Section: Discussionmentioning
confidence: 97%
“…One patient (#7) underwent commercial testing for multiple cancer genes, and a heterozygous PALB2 pathogenic variant (c.1675_1676inv [p. Gln559*]) and a heterozygous NBN pathogenic variant (c.265C>T [p. Arg89*]) were identified that has been reported elsewhere. 20 …”
Section: Resultsmentioning
confidence: 99%
“…NBN pathogenic variants are mostly reported in breast cancer, but recent reports link them to pancreatic cancer as well. However, the cumulative incidence or RR has not been reported [16,21].…”
Section: Nbnmentioning
confidence: 99%
“…PALB2 (partner and localizer of BRCA2) is also involved in DNA damage repair and Fanconi anemia, which is strongly associated with breast, ovarian, and pancreatic cancer [15,16]. PALB2 pathogenic germline variants are associated with a 7.18, 2.91, and 2.37 RR of developing female breast, ovarian, and pancreatic cancer, respectively, and their estimated incidence up to age 80 years is 53%, 5%, and 2%-3%, respectively [17].…”
Section: Palb2mentioning
confidence: 99%